2021
DOI: 10.3390/su13158230
|View full text |Cite
|
Sign up to set email alerts
|

Green Finance Innovation and Regional Green Development

Abstract: Through the use of 30 provincial panel datasets covering the years from 2013 to 2017, on the basis of constructing the regional green development indicator system, this paper used the fixed-base range entropy weight method to measure the regional green development level. The difference-in-differences model was used to test the policy effect, the mechanism of the establishment of the green financial reform, and the innovation pilot zone on green development. The results showed that: (1) the establishment of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 41 publications
1
48
0
Order By: Relevance
“…Table 3 shows the following results: (1) The knowledgesharing willingness of enterprises and universities is inversely connected with their respective knowledge-sharing costs k e , k s and is positively correlated with their respective GTI abilities ω e , ω s and marginal revenue coefficients E e , E s , which indicates that GTI ability and marginal revenue are the driving force of GTI and that the knowledge-sharing costs of enterprises and universities depend on their resistance to knowledge sharing. (2) The GTI level of the U-I and enterprise and university revenues are negatively correlated with…”
Section: Comparative Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 shows the following results: (1) The knowledgesharing willingness of enterprises and universities is inversely connected with their respective knowledge-sharing costs k e , k s and is positively correlated with their respective GTI abilities ω e , ω s and marginal revenue coefficients E e , E s , which indicates that GTI ability and marginal revenue are the driving force of GTI and that the knowledge-sharing costs of enterprises and universities depend on their resistance to knowledge sharing. (2) The GTI level of the U-I and enterprise and university revenues are negatively correlated with…”
Section: Comparative Analysismentioning
confidence: 99%
“…A S the economy develops rapidly in developing countries, green technology innovation (GTI) is gaining increasing attention [1] and has become key to promoting an environmentally friendly economy and enhancing sustainable competitiveness [2]. The irreversibility of global weather and environmental pollution requires China's manufacturing industry to transform and upgrade to green tech-nology [3].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of local governments, Wu et al [ 43 ] found that local government green development behaviors such as environmental legislation and regulation can contribute to improvements of regional environmental quality. In terms of central governments, Wang et al [ 44 ] studied the environmental governance capacity of central environmental monitoring mechanisms based on a regression discontinuity design model, and the results of the study showed that central environmental monitoring mechanisms are effective in environmental governance. However, the two kinds of government often play different roles in the face of different environmental powers and responsibilities.…”
Section: Theoretical Basis and Hypothesis Developmentmentioning
confidence: 99%
“…Compared with other innovation activities, green innovation is not only capital intensive, but also associated with high levels of risk, long cycles, and also requires long-term and stable financial support for enterprises to carry out green innovation activities [79]. Solving the problem of financial constraints is a key factor in promoting green innovation [80,81]. Regional happiness plays an important role in improving the efficiency of resource integration and promoting corporate green innovation, because high levels of local happiness play a positive role in enhancing interpersonal communication and social trust.…”
Section: Hypotheses Developmentmentioning
confidence: 99%